Response of heifers fed Optaflexx™ to supplemental protein - Walker, D.K.; Loe, E.R.; Webb, A.S.; Titgemeyer, Evan C.; Drouillard, James S.; Depenbusch, Brandon E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experiment was conducted to determine the relationship between metabolizable protein supply and feeding Optaflexx™ (ractopamine-HCl) on growth and carcass characteristics of feedlot heifers. Seventy-two crossbred heifers (initially weighing 1048 lb) were fed diets based on steam-flaked corn. Treatments were arranged as a 2 × 3 factorial and included: 0 or 2 grams per heifer daily of Optaflexx™ (0 or 200 mg/day ractopamine-HCl), and diets containing one of three different protein sources (urea, solvent soybean meal, and expeller soybean meal). Optaflexx™ was fed for the final 28 days before slaughter. Optaflexx™ improved daily gain, feed efficiency, carcass-adjusted daily gain, and carcass-adjusted feed efficiency. Responses in gain and efficiency based on final live weights were dependent on protein source; for heifers fed no Optaflexx™, performance was best with expeller soybean meal, whereas performance was best with urea-based diets when Optaflexx ™ was added to diets. Gains and efficiencies based on carcass weights were not affected by dietary protein source. Final live weights were 20 lb greater and carcass weights were 15 lb greater when heifers were fed Optaflexx™. Carcass characteristics were impacted little by either Optaflexx™ or dietary protein source. It does not seem that dietary metabolizable protein supply needs to be increased from that of typical finishing diets to achieve maximum response to Optaflexx™.
Keywords: Beef; Optaflexx; Protein